NLRP3 promotes allergic responses to birch pollen extract in a model of intranasal sensitization - Bauer, Renate; Dang, Hieu-Hoa; Neureiter, Daniel; Unger, Michael Stefan; Neuper, Theresa; Jensen, Melanie; Taliento, Alice Emma; Strandt, Helen; Gratz, Iris; Weiss, Richard; Sales, Angelika; Horejs-Hoeck, Jutta (Frontiers in Immunology, 2024)
Introduction & Objective Allergic sensitization is an essential step in the development of allergic airway inflammation to birch pollen (BP); however, this process remains to be fully elucidated. Recent scientific advances have highlighted the importance of the allergen context. In this regard, microbial patterns (PAMPs) present on BP have attracted increasing interest. As these PAMPs are recognized by specialized pattern recognition receptors (PRRs), this study aims at investigating the roles of intracellular PRRs and the inflammasome regulator NLRP3. Methods We established a physiologically relevant intranasal and adjuvant-free sensitization procedure to study BP-induced systemic and local lung inflammation. Results Strikingly, BP-sensitized Nlrp3-deficient mice showed significantly lower IgE levels, Th2-associated cytokines, cell infiltration into the lung, mucin production and epithelial thickening than their wild-type counterparts, which appears to be independent of inflammasome formation. Intriguingly, bone-marrow chimera revealed that expression of NLRP3 in the hematopoietic system is required to trigger an allergic response. Conclusion Overall, this study identifies NLRP3 as an important driver of BP-induced allergic immune responses.